Ein Textvorschlag zu Ov. met. 1.591 - Gärtner, Thomas (Exemplaria Classica, 2010)
In Ov. met. 1.591, where the majority of manuscripts has Altorum nemorum, the deixis necessitated by the context is provided by the emendation En horum nemorum.